EFEKTIVITAS MODEL EVALUASI PEMBELAJARAN AL-QURAN HADITS PADA SISWA MTS PONDOK PESANTREN PUTERI ATTAQWA DI MASA PANDEMI COVID-19 - Taqiyuddin Taqiyuddin; Ismail Marzuki (Universitas Muhammadiyah Tangerang, 2021)
This study was conducted to determine the effectiveness of the Al Qur'an and Hadith learning evaluation model for students of MTs Pondok Pesantren Puteri Attaqwa during the Covid-19 pandemic. The method in this study uses descriptive qualitative techniques. The data in this study were obtained through interviews and analysis of the value of learning outcomes. The results of the study indicate that the evaluation model for learning the Qur'an and Hadith in MTS students at the Attaqwa Islamic Boarding School for Girls is not effective because it has various limitations.